Cinnamtannin B-1 Prevents Ovariectomy-Induced Osteoporosis via Attenuating Osteoclastogenesis and ROS Generation - Meng Li; Li Hao; Lei Li; Lei Liu; Guang Chen; Wei Jiang; Wei Xu; Chen Zhu; Gang Yao; Shiyuan Fang (Frontiers Media S.A., 2020)
Osteoporosis (OP) is one of the common bone metabolic diseases that endangers postmenopausal women and the elders. Both excessive bone resorption caused by osteoclast over-activation and increased oxidative stress are associated with osteoporosis. Cinnamtannin B-1 (CB-1) is considered as a high-valued plant extract monomer due to its antioxidant properties. However, the mechanism of CB-1 impacts on reducing oxidative stress, inhibiting the production of reactive oxygen species (ROS) and osteoclast differentiation and preventing ovariectomy-induced osteoporosis are still unclear. In this study, the effects of CB-1 on nuclear factor κB (RANKL)-induced osteoclasts formation and differentiation in vitro and the potential therapeutic effect on ovariectomy (OVX)-induced osteoporosis in vivo are investigated. CB-1 was found to inhibit osteoclast formation and bone resorption function in a dose-dependent manner, and it inhibited specific genes related to osteoclast as well. Micro-CT and histopathological staining showed that CB-1 can effectively prevent OVX-induced osteoporosis. In addition, CB-1 treatment can effectively inhibit the production of reactive oxygen species (ROS) in vivo and in vitro. Mechanistically, CB-1 inhibits the activation of osteoclasts by inhibiting the activation of the NF-κB signaling pathway. In conclusion, CB-1 would be able to be used as a promising new drug strategy to inhibit RANKL-induced osteoclastogenesis and prevent ovariectomy-induced osteoporosis.